PENGARUH MEDIA BONEKA TANGAN TERHADAP KEMAMPUAN BERBICARA ANAK SPEECH DELAY USIA KELOMPOK B DI TK ANUGERAH DAN SEKOLAH ANAK BERKEBUTUHAN KHUSUS MEDAN - Dewinta Dewinta Sari; Suri Handayani Damanik (STKIP Subang, 2026)
The purpose of this study is to what extent hand puppet media affect the speaking ability of children with speech delay age group B at Anugerah Kingdegarten and Special Needs School Medan in the 2025/2026 Academic Year. Through a quantitative method with a Pre-Ekperimental model of One Group Pretest-Posttest Design. This study involed 5 children identified as Speech Delay. Observation techniques were used to collect data, then processed statistically using the Shapiro-Wilk test, Wilcoxon Signed Rank Test, and N-Gain with the help of SPSS software. The results showed an increase in the average scre of the intial condition (pretest) of 2,6 and the final score (posttest) reached 4,8 with a difference of 2,2. The normality test confirmed that the data was not normally distributed, because the signicance value of the intial score of 0,046 and the final score 0,006 was smaller than 0,5. Furthermore, the results of the Wilcoxon Signed Rank Test produced a value of 0,034 < 0,05 which means H0 was rejected and Ha was accepted. These figures demonstrate that the use of hand puppet significantly impacts children’s speaking ability. The N-Gain test results showed an average of 0,01787, which is considered low. Although the improvement in speaking ability was not optimal, all children showed improvement after treatment. It can be concluded that there is a significant impact on the speech development of children with speech delays. Therefore, hand puppets are highly recommended as learning tool to help stimulate children’s speech in a more engaging and interactive way.